Konsep Pendidik dalam Pandangan Imam al-Ghazali - Al Hamid, Ahmad; Akbar, Aziz; Rahman, Arif (Adabuna : Jurnal Pemikiran dan Pendidikan, 2023)
Education is very important in one's life, and the progress of a nation is also determined by the education of society in general. And the quality of education depends on the educators. An educator is not just a tutor or teacher who only conveys knowledge, but must carry out an educational process that is oriented towards efforts to build a more established character and that leads to noble character and ethics in everyday life including a good work ethic. This study aims to see how an educator is based on the views of Imam Ghazali. This research is a type of library research, namely research that uses literature, such as books, notes or previous research as the main reference material, then an analysis of the data is carried out. The results of the analysis obtained are that an educator is not only tasked with transferring knowledge but must pay attention to the development of the morals of his students, and an educator must educate with compassion and without distinguishing the status of his students.